1996
DOI: 10.1111/j.1365-2133.1996.tb03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cardiomyopathy in dystrophic epidermolysis bullosa

Abstract: Two unrelated children with autosomal recessive dystrophic epidermolysis bullosa (RDEB) developed fatal dilated cardiomyopathy. Both were malnourished and had severe growth problems. We believe that the most likely cause for the cardiomyopathy is a micronutrient deficiency, most probably selenium deficiency, since the serum selenium level was found to be reduced in the case in whom we measured this, and in 14 of 25 other children with dystrophic epidermolysis bullosa. Echocardiographic screening of 18 other pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
2
14
1
Order By: Relevance
“…In EB, selenium can play a role in the emergence of DC, but is unlikely to be the only causal factor. Some EB patients with DC had normal selenium levels (3,7), as well as five of our patients. Selenium was not significantly lower in EB patients with DC as reported by Sidwell et al (4), when compared with EB patients without DC.…”
Section: Discussionsupporting
confidence: 68%
“…In EB, selenium can play a role in the emergence of DC, but is unlikely to be the only causal factor. Some EB patients with DC had normal selenium levels (3,7), as well as five of our patients. Selenium was not significantly lower in EB patients with DC as reported by Sidwell et al (4), when compared with EB patients without DC.…”
Section: Discussionsupporting
confidence: 68%
“…All the echocardiograms performed in 18 patients were normal. 5 In our series, free carnitine was low in 61.5% of the patients but the ratio free carnitine/total carnitine was between 43 and 68%, which is not very low and is possibly explained by the morning fast. Total carnitine was slightly decreased in one case (patient with a gastrostomy), probably related to a severe protein deficiency (albumin < 30 g/L, RBP 11 mg/L).…”
Section: Total Carnitinecontrasting
confidence: 57%
“…10 Selenium deficiency has been observed in two patients with dystrophic epidermolysis bullosa who both developed dilated cardiomyopathy. 12 The clinical presentation of this patient resembled the cases reported by Leiner in 1908, 13 characterized by congenital erythroderma, failure to thrive and diarrhoea. Although it was later shown that patients with 'Leiner's disease' belong to several subgroups (Netherton's syndrome, ichthyosiform erythroderma, Omenn's syndrome and others), 14 they share the same clinical features and have a high mortality of between 30 and 50%.…”
Section: Discussionsupporting
confidence: 77%